The life and adventures of Sir Launcelot Greaves - Smollett, T. (Tobias), 1721-1771 (Smollett, T. (Tobias), 1721-1771. Works. 1988., 2002)
"This new edition brings to life Tobias Smollett's fourth novel, The Life and Adventures of Sir Lancelot Greaves. No annotated edition of the work existed before the second half of the twentieth century, and this comprehensive edition by Robert Folkenflik and Barbara Laning Fitzpatrick features more accurate text as well as scrupulous textual and critical information. Also included in the detailed introduction is a unique examination of Sir Launcelot Greaves, the first illustrated serial novel, in relation to the engravings by Anthony Walker."--Jacket